Soft tissue facial profile and anteroposterior lip positioning in Iranians - GhorbanyJavadpour, Fataneh; Khanemasjedi, Mashaallah (Journal of Dental School, 2019)
Objective: Since orthodontic and orthognathic treatment planning in each ethnic group must be done according to the soft tissue facial characteristics regarded as beauty, they thus vary from country to country. The main purpose of this articlewas to determine the mean range of the middle third of soft tissue facial profile and anteroposterior lip positioning using 3angular and 2 linear measurements in adult male and female Iranians to compare with European standards. Methods: After clinical examination of 180 dental students, 70 Iranian adults who had normal occlusion aged between 21 to 29 years (mean:24.5 years) were selected(35 males and 35females). After obtaining consent form, lateral cephalograms were taken in natural head position (NHP) (as seen in a mirror) and analyzed according to the Rickets(E-Line),Tweed-Merrifield(Z-angle) and Holdaway (H-angle).For comparison of data with standards, the One-Sample-t-test and for comparison of measurements between groups, Independent Sample-t-test was used. Results: Radiographic evaluation revealed that all Iranian samples had significant differences with European standards with no differences between males and females. In the Rickets (E-Line) analysis, both upper (p<0.001)and lower(p<0.01) lips were behind the E-line. In the Tweed- Merrifield (Z-angle) analysis this angle in the Iranian sample was smaller (p<0.001) and in the Holdaway (H-angle) analysis our sample had smaller H-angle as well (p<0.001). Conclusion: Iranian adults have retruded upper and lower lip position in both sexes and more convex profile than European standards; thismay be due to a more retruded position of the chin and lips or more prominence of the nose in Iranian samples.